Hsp27-Actin Interaction - Philip Graceffa (Biochemistry Research International)
Hsp27 oligomer is reported to interact with F-actin as a barbed-end-capping protein. The present study determined the binding strength and stoichiometry of the interaction using fluorescence of probes attached to Hsp27 cysteine-137. The fluorescence of acrylodan attached to Hsp27 increased 4-5-fold upon interaction with F-actin. Titration of the fluorescence with F-actin yielded a weak binding constant (KDapp=5.3 μM) with an actin/Hsp27 stoichiometry between < 1 and 6. This stoichiometry is inconsistent with an F-actin end-capping protein. Pyrene attached to Hsp27 exhibited a large excimer fluorescence, in agreement with the known proximity of the cysteine-137's in the Hsp27 oligomer. Upon interaction with F-actin the pyrene-Hsp27 excimer fluorescence was largely lost, suggesting that Hsp27 interacts with F-actin as a monomer, consistent with the acrylodan-Hsp27 results. EM images of F-actin-Hsp27 demonstrated that Hsp27 is not a strong G-actin sequester. Thus, Hsp27, in vitro, is a weak F-actin side-binding protein.